Unit 12.33 A Rapid and Sensitive Automated Image‐Based Approach for In Vitro and In Vivo Characterization of Cell Morphology and Quantification of Cell Number and Neurite Architecture. Issue 1 (1st April 2014) - Tapias, Victor; Greenamyre, J. Timothy
Abstract: Stereological methods for tissue cell counting, specifically for neuron quantification, decrease systematic error and sampling bias; however, they are tedious, labor intensive, and time consuming. Approaches for cell (neuron) quantification in vitro are not accurate, sensitive, or subsequently reproducible. Neuronal phenotype is related to alterations in cell morphology and neurite pattern. The techniques currently available for quantification of these features present several limitations. In this unit, we provide validated automated procedures for in vivo and in vitro quantification of cell number, morphological cell changes, and neurite morphometry in a fast, simple, and reliable manner. Our method counts up to 8 times as many neurons in less than 5% to 10% of the time required for stereological analysis (optical fractionator). In summary, this technology offers an unparalleled opportunity to examine features of cells at high resolution in a complex three‐dimensional environment. These techniques provide an exceptional in vivo and in vitro system for neurotoxicity studies, disease modeling, and drug discovery. Curr. Protoc. Cytom . 68:12.33.1‐12.33.22. © 2014 by John Wiley & Sons, Inc.